Managing in Translation: A Theoretical Model - Farghal, Mohammed (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractThe present paper aims to shed light on the notion of managing in the process of translating. It firmly distinguishes between two types of managing: Intrinsic vs. Extrinsic managing. Intrinsic managing, on the one hand, is entailed by the numerous asymmetries existing between the SL and TL, thus aiming to bring about natural naturalations. Extrinsic managing, on the other hand, is the translator's ideological superimposition on the SL text, thus steering it in a way as to meet his own goals. It is demonstrated that these two types of managing may operate at different levels in the process of translating, viz, syntactic, semantic, pragmatic, textual and cultural levels. The paper argues that intrinsic managing is inevitable, hence is commendable; whereas, extrinsic managing constitutes the translator's premeditated intervention in the message of the SL text, hence is condemnable.